Polymorphism in ftsI gene and ß-lactam susceptibility in Portuguese Haemophilus influenzae strains: clonal dissemination of β-lactamase-positive isolates with decreased susceptibility to amoxicillin-clavulanic acid - Barbosa, Ana Raquel (2011)
OBJECTIVES: The aim of this study was to characterize ampicillin resistance mechanisms in clinical isolates of Haemophilus influenzae from Portugal. Association between specific patterns of amino acid substitutions in penicillin-binding protein 3 (PBP3) (with or without β-lactamase production) and β-lactam susceptibility as well as genetic relatedness among isolates were investigated. METHODS: Two-hundred and forty non-consecutive H. influenzae isolates chosen according to their different ampicillin MICs [101 β-lactamase-non-producing ampicillin-resistant (BLNAR) isolates, 80 β-lactamase-producing ampicillin-resistant (BLPAR) isolates and 59 β-lactamase-non-producing ampicillin-susceptible (BLNAS) isolates] were analysed. The β-lactamase-encoding bla(TEM-1) gene was detected by PCR. The ftsI gene encoding PBP3 was sequenced. Genetic relatedness among isolates was examined by PFGE. RESULTS: Of the 240 H. influenzae isolates, 141 had mutations in the transpeptidase domain of the ftsI gene, including most BLNAR strains (94/101, 93.1%) and a high percentage of BLPAR strains (47/80, 58.8%). As previously reported, the latter have been described as β-lactamase-positive amoxicillin/clavulanic acid resistant (BLPACR). The most common amino acid substitutions were identified near the KTG motif: N526K (136/141, 96.5%), V547I (124/141, 87.9%) and N569S (121/141, 85.8%). The 141 strains were divided into 31 ftsI mutation patterns and included six groups (I, IIa, IIb, IIc, IId and III-like). BLNAR strains were genetically diverse but close genetic relationships were demonstrated among BLPACR strains. CONCLUSIONS: This study shows that the non-enzymatic mechanism of resistance to β-lactams is widespread among H. influenzae isolates in Portugal. Clonal dissemination of BLPACR strains showing high resistance to ampicillin and reduced susceptibility to amoxicillin/clavulanic acid was documented.